Jurnalisme Imersif dan Partisipasi Publik dalam Industri Media - Clara Ariski Paramitha (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2022)
This article aims to introduce the concept of immersive journalism as a new genre in digital journalism. Hierarchy of influence is used to understand the condition of immersive journalism in the media industry. This article describes the condition of digital journalism in Indonesia and the concept of immersive journalism using the literature review method. The results of the analysis show that the production, distribution, and consumption processes of news are influenced by internal and external media organizations. The public participation opportunity that has been created in digital journalism has the potential to sustain in immersive journalism. The audience can actively participate and have control over narrative construction. A series of challenges in the development of immersive journalism that have been identified include business potential, adaptation of supporting tools, narrative creation, and vulnerability to manipulation. The dilemmatic problems faced by media industry players will be even more complex if they apply immersive journalism: redefining with the audience the limits of participation, narrative framing, objectivity, and sensitive content.ABSTRAK Artikel ini bertujuan untuk memperkenalkan konsep jurnalisme imersif sebagai genre baru dalam jurnalisme digital. Teori hierarki pengaruh digunakan untuk memahami kondisi jurnalisme imersif dalam industri media. Tulisan ini memaparkan kondisi jurnalisme digital di Indonesia dan konsep jurnalisme imersif dengan menggunakan metode kajian literatur. Hasil analisis menunjukkan proses produksi, distribusi, hingga konsumsi berita dipengaruhi oleh internal dan eksternal organisasi media. Ruang partisipasi publik yang telah terbentuk dalam jurnalisme digital, memiliki potensi keberlanjutan dalam jurnalisme imersif ketika khalayak dapat berpartisipasi aktif dan memiliki kendali terhadap konstruksi narasi. Serangkaian tantangan dalam prengembangan jurnalisme imersif yang telah diidentifikasi antara lain potensi bisnis, adaptasi piranti penunjang, pembuatan narasi, dan kerentanan manipulasi. Permasalahan dilematis yang dihadapi pelaku industri media akan semakin kompleks jika menerapkan jurnalisme imersif: merumuskan kembali bersama khalayaknya batasan partisipasi, pembingkaian narasi, objektivitas, serta konten sensitif.